Through teachers’ eyes: adaptability and transformations in their practices and relationship with students during COVID-19 pandemic - Dario, Nadia; Mollo, Monica; Savarese, Giulia; Carpinelli, Luna (Frontiers in Education, 2024)
Introduction This research critically and empirically analyzes the intricate interaction between the transformative impact of the COVID-19 pandemic on the Italian educational system and the quality of the teacher-student relationship. The main focus is on the experiences of Italian educators who had to deal with the upheavals caused by the pandemic within an educational system. Aim The primary purpose of this study is to explore (a) how did teachers’ educational practices change during the first lockdown and (b) how did the teacher-student relationship evolve during the first lockdown from the teachers’ point of view. Methods The study uses a qualitative approach through semi-structured interviews and diary collection (conducted via platforms). Participants are Italian primary and secondary school teachers aged between 25 and 60. Results In this study, the thematic analysis of the content of the interviews and diaries reveals: the initial responses of educators, the transition to distance learning, the challenges and potential of virtual education, the students’ evaluation, future perspectives, and the topic of the relationship with students (particularly addressed in the diaries). Discussion By delving into the transformation of the teacher-student relationship under extraordinary circumstances, this research enriches the discourse on its quality, capturing the psychological nuances of learning-teaching experiences, and uncovers the multifaceted transformations in teaching methodologies, tools, and assessments.